Public-Private Partnerships: an International Development vis a vis Indonesia Experience - RIZAL YAYA (Jurnal Studi Pemerintahan, 2014)
For more than two decades, Public Private Partnerships(PPP) had developed worldwide as an instrumentto procure public infrastructure where governmentfunds are limited. This practice supports thecovergent theory of the public and private sector.Indonesia experience with PPP follows most of whathad been done by countries overseas with somedeviations. The main reasons for going for PPP forIndonesia government is to fill the gap in financeand capability in procuring the infrastructure. Unofficialreason such as for off-balance sheet and ideologicalis not relevant. Up to now, the Governmentonly allow investment in hard economic infrastructure.Instead of using pure private finance, IndonesiaGovernment facilitates public funds either fromCentral Government or Local Governments to financePPP projects. In most cases, this involvementis because of marginality of the project. This resultsin the condition where the Government still hasdominant role in the existing PPP projects. Comparedto the PPP framework in other countries likein the UK, Indonesia PPP lacks of attention on outputspecification and risk transfer. This may be becauseof lacking of experiences as well as due tohigh degree of Government involvement. Rigorouspolicy is needed in this area to ensure Governmentto achieve better value for money.Keywords: Public-Private Partnerships, Public InfrastructureProcurement, International PPP, IndonesiaPPP, value for money mechanism